Mechanical and Tribological behavior of hemp Fiber Reinforced Polymeric Composites - L.Vadivel Kannan (International Journal of Modern Agriculture, 2021)
In recent years, there has been an increasing interest in finding new applications for natural fibre-reinforced composites that are traditionally used for making ropes, mats, carpets, fancy articles and others. This work presents the evaluation of mechanical and tribological behaviour of hemp fiber reinforced epoxy composites. The composites were prepared by varying the weight percentage (wt %) 30%, 40% and 50% wt %of chopped fibre of 10mm length. The specimens are expurgated as per the ASTM standards. The Mechanical properties such as flexural strength, impact strength and hardness were revealed of the fabricated hemp fiber reinforced composite. The test results show that the higher value of hardness and impact was obtained at 50wt. % of fiber loading. The Flexural and Tensile strength value is higher in 40wt. % of fiber loading. It has a wide scope in the areas of construction, auto motives and aviation industries.